2022
DOI: 10.3390/genes13020276
|View full text |Cite
|
Sign up to set email alerts
|

Expanding Phenotype of Poirier–Bienvenu Syndrome: New Evidence from an Italian Multicentrical Cohort of Patients

Abstract: Background: Poirier–Bienvenu Neurodevelopmental Syndrome (POBINDS) is a rare disease linked to mutations of the CSNK2B gene, which encodes for a subunit of caseinkinase CK2 involved in neuronal growth and synaptic transmission. Its main features include early-onset epilepsy and intellectual disability. Despite the lack of cases described, it appears that POBINDS could manifest with a wide range of phenotypes, possibly related to the different mutations of CSNK2B. Methods: Our multicentric, retrospective study … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(18 citation statements)
references
References 17 publications
(64 reference statements)
1
17
0
Order By: Relevance
“…POBINDS is a very rare autosomal dominant genetic disorder (1). Poirier et al in 2017 provided the first report of mutations in the CSNK2B gene in two unrelated patients with neurodevelopmental abnormality and epilepsy; since then, a total of 57 patients with pathogenic mutations in this gene have been described (1,2,(14)(15)(16)(17)(18)(19)(20). The most frequent manifestations of these subjects with mutations in the CSNK2B gene are epilepsy, developmental delays, and intellectual disabilities (Tables 1, 3).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…POBINDS is a very rare autosomal dominant genetic disorder (1). Poirier et al in 2017 provided the first report of mutations in the CSNK2B gene in two unrelated patients with neurodevelopmental abnormality and epilepsy; since then, a total of 57 patients with pathogenic mutations in this gene have been described (1,2,(14)(15)(16)(17)(18)(19)(20). The most frequent manifestations of these subjects with mutations in the CSNK2B gene are epilepsy, developmental delays, and intellectual disabilities (Tables 1, 3).…”
Section: Discussionmentioning
confidence: 99%
“…CSNK2B deficiency alters neuron development and synaptic transmission, resulting in severe neurodevelopmental deficiencies (12,13). Recently, 57 unrelated patients with Poirier-Bienvenu neurodevelopmental syndrome and de novo mutations in the CSNK2B gene have been described (1,2,(14)(15)(16)(17)(18)(19)(20). The phenotypes of these patients were heterogeneous and included treatable or untreatable seizures, mild-to-profound intellectual disabilities/or learning disabilities, language delays, and other symptoms (1,2,(14)(15)(16)(17)(18)(19)(20).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…During the finalization of the study and manuscript preparation, patients 1, 8, 9, and 10 were eventually presented in a frame of more extensive gene-specific cohort description. These results allowed us to confirm a specific electroclinical syndrome ( SLC13A5 ), to add new elements to known DEEs or NDDs ( SPATA5 , CSNK2B ), and to substantiate a candidate gene as a disease gene ( SPEN ) [ 39 , 40 , 41 , 42 ].…”
Section: Resultsmentioning
confidence: 99%
“…Conversely, variants in CSNK2B have recently been associated with the Poirier-Bienvenu neurodevelopmental syndrome (MIM: #618732), a neurological disorder characterised by early-onset and possibly refractory seizure, intellectual disability of various degree, and ASD. The c.384_394delAGGTGAAGCCA, p.(Pro128fs) frameshift variant was identified in the proband at the heterozygous state and has recently been reported as pathogenic in a small cohort of Poirier-Bienvenu patients [ 28 ]. Familial segregation analysis confirmed that both variants originated de novo in the proband.…”
Section: Resultsmentioning
confidence: 99%